Evaluation of In-Vivo Gastro Protective Activity of Various Extract of Ventilago Maderaspatana Bark Induced by HCl - Ethanol in Rats (International Journal of Research in Pharmaceutical Sciences and Technology, 2026)
Ventilago maderaspatana bark is traditionally used for the treatment of gastric ulcers. The present study evaluated the gastroprotective activity of chloroform and ethanolic extracts of Vexxntilago maderaspatana bark against HCl–ethanol–induced ulcer lesions in rats. Methodology: Shade-dried bark was powdered and extracted with chloroform and ethanol by continuous hot percolation using a Soxhlet apparatus. Gastric ulcers were induced by oral administration of an HCl–ethanol mixture, and animals were divided into six groups: group 1, negative control; group 2, standard drug sucralfate (100 mg/kg); group 3, chloroform extract (100 mg/kg); group 4, chloroform extract (200 mg/kg); group 5, ethanolic extract (100 mg/kg); and group 6, ethanolic extract (200 mg/kg). Results: In the negative control group, the ulcer index was 7.20 ± 0.72 with no ulcer inhibition. Sucralfate (group 2) produced an ulcer index of 2.50 ± 0.25 and 65.27% ulcer inhibition. Chloroform extract at 100 and 200 mg/kg (groups 3 and 4) showed ulcer indices of 6.50 ± 0.65 and 5.50 ± 0.55, corresponding to 9.72% and 23.61% inhibition, respectively. Ethanolic extract at 100 and 200 mg/kg (groups 5 and 6) produced ulcer indices of 4.20 ± 0.42 and 2.90 ± 0.29, with 41.66% and 59.72% inhibition, indicating a dose-dependent gastroprotective effect. Conclusions: The ethanolic bark extract of Ventilago maderaspatana exhibited marked, dose-dependent gastroprotective activity in the HCl–ethanol model, approaching the efficacy of sucralfate, whereas the chloroform extract was comparatively less active, supporting the traditional use of this plant.
Keywords: Antiulcer activity; chloroform; ethanol; sucralfate; Ventilago maderaspatana